Tingkat Pengetahuan Beyond Use Date di Kalangan Orang Tua yang Memiliki Balita di Klinik Sunda Medika Kab. Indramayu - Zeny Dermawan; Sri Setiatjahjati; Aulia Zazirotul (STIKes Ibnu Sina Ajibarang, 2025)
Public knowledge of Beyond Use Date (BUD) is still low, whereas to ensure the safety of drug use, an understanding of these two things is needed. This study aims to determine the level of public knowledge and behavior regarding BUD on the drugs they consume. This type of research uses quantitative descriptive analysis with a cross-sectional design. The sample used in this study was 164 respondents and data collection was through a questionnaire. The results of the study showed that the level of public knowledge regarding BUD was good in female respondents reaching 58% (80 people), and the sufficient category was 42% (58 people). While the research data on good behavior in implementing BUD were women with the highest sufficient category recording 55.8% (77 people), and the good category was 44.2% (61 people). A correlation test using Spearman Rank also showed significant results between knowledge and behavior in female respondents regarding BUD with a p value of 0.000 (≤0.05). This study interprets the importance of increasing public knowledge about Beyond Use Date (BUD) to help improve behavior in using drugs safely and effectively.